2022
DOI: 10.1016/j.isci.2021.103722
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection enhances mitochondrial PTP complex activity to perturb cardiac energetics

Abstract: SARS-CoV-2 is a newly identified coronavirus that causes the respiratory disease called coronavirus disease 2019 (COVID-19). With an urgent need for therapeutics, we lack a full understanding of the molecular basis of SARS-CoV-2-induced cellular damage and disease progression. Here, we conducted transcriptomic analysis of human PBMCs, identified significant changes in mitochondrial, ion channel, and protein quality-control gene products. SARS-CoV-2 proteins selectively target cellular organelle compartments, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 52 publications
5
35
0
Order By: Relevance
“…A previous study reported that mitochondrial metabolism was disturbed by SARS-CoV-2 infection, and enhanced mitochondrial permeability transition pore (PTP) activity has been observed upon the virus infection in human PBMCs [38] . In another report, a transcriptome databank of cell and clinical samples revealed that cellular respiration proteins and the complex I were downregulated by SARS-CoV-2 infection [39] .…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that mitochondrial metabolism was disturbed by SARS-CoV-2 infection, and enhanced mitochondrial permeability transition pore (PTP) activity has been observed upon the virus infection in human PBMCs [38] . In another report, a transcriptome databank of cell and clinical samples revealed that cellular respiration proteins and the complex I were downregulated by SARS-CoV-2 infection [39] .…”
Section: Resultsmentioning
confidence: 99%
“… 174 , 183 , 186 , 187 Notably, mPTP blocker cyclosporin A was demonstrated to protect cardiomyocytes from SARS‐CoV‐2‐induced autophagy and cell death. 183 …”
Section: Mechanisms Of Remodeling Host Metabolism By Sars‐cov‐2mentioning
confidence: 99%
“… 182 Viral proteins ORF9c, M, Nsp6, and ORF3a were shown to localize to mitochondrial membrane and induce morphological changes. 183 Of note, viral proteins encoded by SARS‐CoV‐2 genome were reported to interact with multiple proteins located in mitochondrial inner membrane. Mitochondrial permeability transition pore (mPTP) is a protein complex formed in the inner membrane under specific pathological conditions.…”
Section: Mechanisms Of Remodeling Host Metabolism By Sars‐cov‐2mentioning
confidence: 99%
See 2 more Smart Citations